2019
DOI: 10.1029/2019gl082218
|View full text |Cite
|
Sign up to set email alerts
|

Wind in Jezero Crater, Mars

Abstract: Wind generates erosional and depositional morphologies across Mars, including in Jezero crater, the planned landing site for the Mars 2020 rover. Known for subaqueously formed sedimentary features, Jezero crater also hosts wind‐formed features that provide insights about the local wind regime. We combine interpretations from dunes, wind streaks, transverse aeolian ridges, and yardangs to holistically understand the recent history of wind in Jezero crater. Together, these features describe modern easterly winds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…Eolian erosion formed the ridged surface in the northeastern portion of unit Nue (fig. 3A) and the ridges are interpreted as yardangs (Day and Dorn, 2019). Erosion of local or regional units continued to contribute to the deposition of the dark-colored mantle overlying units Njf and Nnp 1 and collecting in topographically lower regions.…”
Section: Late Hesperian To Late Amazonianmentioning
confidence: 97%
See 3 more Smart Citations
“…Eolian erosion formed the ridged surface in the northeastern portion of unit Nue (fig. 3A) and the ridges are interpreted as yardangs (Day and Dorn, 2019). Erosion of local or regional units continued to contribute to the deposition of the dark-colored mantle overlying units Njf and Nnp 1 and collecting in topographically lower regions.…”
Section: Late Hesperian To Late Amazonianmentioning
confidence: 97%
“…In contrast to other linear features in the map area, such as the "ridge crest" feature in unit Nnp 1 , the ridges in the ridged surface of unit Nue tend to be shorter-on the scale of a few hundred meters in length at mostand are more closely spaced (tens of meters to a hundred meters). These ridges are interpreted as yardangs (Day and Dorn, 2019). Although texturally distinct from the other parts of unit Nue, we could not confidently place the stratigraphic transition between the ridged surface and the rest of unit Nue, thus we mapped this surface texture as part of unit Nue and used the "ridged surface" to indicate the extent of this texture.…”
Section: Mapped Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The approximate position of the landing ellipse of the rover Manuscript submitted to Geophysical Research Letters and the potential traversable routes of the rover to regions of interest within the landing site surrounds the partially eroded delta deposits (also known as western delta deposit) at the mouth of the western inlet channel (Figure 1b; Fassett and Head, 2005;Goudge et al, 2015Goudge et al, , 2017Farley, 2018;Mangold et al, 2020;Williams et al, 2020). Presence of aeolian landforms such as yardangs and transverse aeolian ridges (TARs) has been reported over the volcanic deposits on the front of the delta deposits (Chojnacki et al, 2018;Day and Dorn, 2019), and aeolian erosion has been suggested to have extensively eroded the delta deposits (Fassett and Head, 2005;Schon et al, 2012). In addition, the front of ~50-60 m high western delta deposit hosts numerous boulders on its top surface, over its talus slope and at the base of the talus slope.…”
Section: Introductionmentioning
confidence: 99%